Cerebral fat embolism without intracardiac shunt: A novel presentation - Eriksson, Evert A (Medknow Publications, 2011)
Fat embolism syndrome (FES) is defined as an uncommon life-threatening disease process consisting of pulmonary, central nervous system (CNS), and cutaneous manifestations. The pathophysiology of this secondary injury is poorly understood. In the setting of the multiply injured patient, the diagnosis of FES is difficult to ascertain. A case report of a posttraumatic death caused by acute dissemination of diffuse fat emboli to the brain and lungs in the absence of a right-to-left heart defect after femur fracture is presented. The transesophageal echo cardiogram with bubble study failed to demonstrate an intracardiac defect or AV malformation in the lung further supporting a biochemical process. The acute decompensation of the patient within 2 h of the injury would favor mechanical emboli. Supportive care continues to be the mainstay of treatment for FES. Cerebral fat embolism should be considered in traumatically injured patients with unexplained decline in their neurologic examination. Cerebral fat embolism may occur without an intracardiac shunt.